Ambiguous fear in the war on drugs: A reconfiguration of social and moral orders in the Philippines. (June 2020) - Warburg, Anna Bræmer; Jensen, Steffen
Abstract : This article explores the social and moral implications of Duterte's war on drugs in a poor, urban neighbourhood in Manila, the Philippines. Drawing on long-term ethnographic fieldwork, surveys, and human rights interventions, the article sheds light on policing practices, social relations, and moral discourses by examining central perspectives of the state police implementing the drug war, of local policing actors engaging with informal policing structures, and of residents dealing with everyday insecurities. It argues that the drug war has produced a climate of ambiguous fear on the ground, which has reconfigured and destabilised social relations between residents and the state as well as among residents. Furthermore, this has led to a number of subordinate moral discourses — centred on social justice, family, and religion — with divergent perceptions on the drug war and the extent to which violence is deemed legitimate.